Hello, Kwesi74!
I assume you can rewrite from logs to exponentials: \(\displaystyle \log_b(N)\,=\,N\;\longleftrightarrow\;b^x\,=\,N\)
\(\displaystyle \log_x(2x\,+\,3)\:=\:2\)
Rewrite:
.\(\displaystyle x^2\:=\:2x\,+\,3\;\;\Rightarrow\;\;x^2\,-\,2x\,-\,3\:=\:0\)
. . which factors:
.\(\displaystyle (x\,-\,3)(x\,+\,1)\:=\:0\)
. . and has roots:
. \(\displaystyle x\,=\,3,\,-1\)
But -1 cannot be the base of a logarithm.
Therefore, the only answer is: \(\displaystyle x\,=\,3\)
\(\displaystyle \log_2(4x\,+\,1)\:=\:3\)
Rewrite:
.\(\displaystyle 2^3\:=\:4x\,+\,1\;\;\Rightarrow\;\;4x\,+\,1\:=\:8\)
Then:
.\(\displaystyle 4x\:=\:7\;\;\Rightarrow\;\;x\,=\,\frac{7}{4}\)